The Pluralistic Ontology in Youth Groups for Mental Health - Rojas-Andrade, R (BRISTOL UNIV PRESS & POLICY PRESS, 2024)
Mental problems in young people are increasing and recovery proposals from classic biomedical models are not always effective. One of the responses to this has been the Mutual Help Groups, groups made up of people who meet periodically to help each other based on principles such as trust, transversality, the creation of support networks and new possibilities for psychosocial recovery. These possibilities arise from the same people, with the help of others, to have new ways of understanding reality and approaching it, which is called the agency of possibilities. This research aims to understand the contribution that Mutual Aid Groups make to young people s mental health through group agency. For this, an analysis is carried out through the Event , an element of the pluralistic ontology of neo-monadism, which is defined as the unification of individualities based on incalculable networks that overlap with each other to generate new questions and new answers. Using thematic analysis as an analysis tool, in-depth interviews were conducted with six young people with mental problems belonging to a Mutual Help Group. There it was found that intentional states broadly explain world-to-mind, mind-to-world and mind-to-mind functional relationships and interactions, which contributes to ontological pluralism as a new paradigm for addressing social problems. Mental health care has long sought to control people. In this sense, negative adaptation guarantees recover y in vain. On the other hand, positive adaptation, from desires, from heterogeneous forces and beliefs, could be a more effective recovery path.